1987
DOI: 10.1288/00005537-198706000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Speaking proficiency variations according to method of alaryngeal voicing

Abstract: Twelve judges, with no previous exposure to laryngectomees, rated the speaking proficiencies of 33 laryngectomees divided into the following groups: 1. esophageal speakers (n=12); 2. electrolarynx speakers (n=11); and 3. tracheoesophageal puncture speakers (n=10). In addition, the speech of ten normal subjects was rated. Specific speaking parameters examined included voice quality, pitch, loudness, intelligibility, rate of speaking, visual presentation during speech, extraneous speaking noise, and overall comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 5 publications
3
59
0
2
Order By: Relevance
“…(4) It has been reported that the voice prosthesis can result in speech that is more similar to laryngeal speech, giving the patient a longer lasting, better quality and more understandable voice. (5) In this study, we aimed to identify the factors that influence the longevity and replacement frequency of voice prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…(4) It has been reported that the voice prosthesis can result in speech that is more similar to laryngeal speech, giving the patient a longer lasting, better quality and more understandable voice. (5) In this study, we aimed to identify the factors that influence the longevity and replacement frequency of voice prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…The valve prosthesis is generally accepted to be the method of choice in suitable patients, and allows production of a voice of superior quality to that achievable by other methods Williams and Watson, 1987;Pindzola and Cain, 1988;Hilgers and Schouwenburg, 1990). In Manchester, as in other centres, the Provox™ valve has gained popularity and is now the most commonly used prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…"18 In this article, we address the issue of success rate variability. The purposes of the article are (1) to intro¬ duce a rating scale that proposes a new conceptualiza¬ tion of success that involves three dimensions, (2) to determine factors that predict tracheoesophageal punc¬ ture success by incorporating this multidimensional rat¬ ing scale in a stepwise multiple regression analysis, and (3) to show how relevant factors can be combined to predict success.…”
mentioning
confidence: 99%